2020
DOI: 10.1021/acs.jpcb.0c03544
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Role of 2,2,2-Trifluoroethanol Solvent Dynamics in Inducing Conformational Transitions in Melittin: An Approach with Solvent 19F Low-Field NMR Relaxation and Overhauser Dynamic Nuclear Polarization Studies

Abstract: 2,2,2-Trifluoroethanol (TFE) is one of the fluoroalcohols that have been known to induce and stabilize an open helical structure in many proteins and peptides. The current study has benchmarked low-field 19 F NMR relaxation and 19 F Overhauser dynamic nuclear polarization (ODNP) by providing a brief account of TFE solvent dynamics in a model melittin (MLT, an antimicrobial peptide) solution with a TFE−D 2 O cosolvent mixture at pH 7.4. Further, this approach has been employed to reveal the solvation of MLT by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The choice of TFE : water ($8 : 2 vol%) and chloroform : methanol : water ($4 : 4 : 1 vol%) as membranemimicking solvents was made because the use of these solvent mixtures for membrane-protein extraction, CD and/or NMR has precedent in the experimental literature. 6,[67][68][69][70] Hydrophobic solvents have also been used to mimic the low polarity of protein binding pockets for CD and NMR experiments of intrinsically disordered protein-binding peptides. 4,71 Following initial simulations, it was observed that the chloroform : methanol : water ($4 : 4 : 1 vol%) mixture separates into two phases when using the CGenFF/DH models (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of TFE : water ($8 : 2 vol%) and chloroform : methanol : water ($4 : 4 : 1 vol%) as membranemimicking solvents was made because the use of these solvent mixtures for membrane-protein extraction, CD and/or NMR has precedent in the experimental literature. 6,[67][68][69][70] Hydrophobic solvents have also been used to mimic the low polarity of protein binding pockets for CD and NMR experiments of intrinsically disordered protein-binding peptides. 4,71 Following initial simulations, it was observed that the chloroform : methanol : water ($4 : 4 : 1 vol%) mixture separates into two phases when using the CGenFF/DH models (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The temporins adopt extended or unstructured conformers in other environments, this conformational phase changes would prevent indiscriminate membranolytic activity and lower the host cell toxicity ( Travkova et al, 2017 ). A previous study about TFE as a peptide stabilizes cosolvent indicated that TFE could help helical peptides maintain their secondary structure by promoting intramolecular hydrogen bond formation and peptides aggregation ( Chaubey et al, 2020 ), therefore reflects the mechanisms of peptide-membrane interaction when the AMPs contact with pathogenic microorganisms. This phenomenon has also been reported in previous studies of temporins ( Mangoni, 2006 ; Sang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chaubey et al observed changes in the dynamics of the solvent 2,2,2-trifluoroethanol (TFE) when the peptide melittin undergoes structural reorganization from a random coil to a helical structure. They measured the DNP enhancement of 19 F by the polarizing agent TEMPOL and used the DNP coupling factor as an indicator of the correlation time of the cosolvent TFE . Hyperpolarized water has also been used to measure protein hydration by increasing the sensitivity of techniques such as fast 2D NMR, exchange spectroscopy (EXSY), and nuclear Overhauser effect spectroscopy (NOESY). …”
Section: Applications Of Liquid-state Dnp Nmrmentioning
confidence: 99%
“…They measured the DNP enhancement of 19 F by the polarizing agent TEMPOL and used the DNP coupling factor as an indicator of the correlation time of the cosolvent TFE. 40 Hyperpolarized water has also been used to measure protein hydration by increasing the sensitivity of techniques such as fast 2D NMR, exchange spectroscopy (EXSY), and nuclear Overhauser effect spectroscopy (NOESY). 41−44 3.2.…”
Section: Applications Of Liquid-state Dnp Nmrmentioning
confidence: 99%